Law on foreign exchange - Chowdhury, A. N. M. Khaled; Bangladesh (Chittagong : Arjuman Chowdhury, 1985)
Commentary, with text and amendments up to 1982, on Foreign Exchange Regulation Act, 1947 of Bangladesh.
Keywords: Foreign exchange -- Law and legislation -- Bangladesh